Case Report: Transcatheter valve implantation in a 13-year-old teenager with critical aortic stenosis and Singleton–Merten syndrome - Pervunina, T. M.; Irtyuga, O. B.; Vershinina, T. L.; Babakekhyan, M. V.; Lyapunova, A. A.; Kostareva, A. A.; Zubarev, D. D.; Gorbatykh, A. V.; Prokhorikhin, A. A.; Grekhov, E. V.; Vasichkina, E. S.; Shlyakhto, E. V. (Frontiers in Cardiovascular Medicine, 2025)
This article presents a rare case of transcatheter aortic valve implantation (TAVI) in a critically ill teenager with Singleton–Merten syndrome. The procedure was successful, and the patient was discharged home without complication. To the best of our knowledge, this is the first report combining disease, age, and TAVI.